Exchange Rate Pass-Through and Economic Openness Under Inflation Targeting Framework in Asian ITF Economies - Akhmad Syakir Kurnia; FX Sugiyanto (Faculty of Economic and Business, 2023)
This study investigates overall ERPT in four ITF-adopting Asian Economies, emphasizing the trilemma between ERPT, economic openness, and the inflation target. Based on quarterly data observations from 1999 to the fourth quarter of 2022 with an application of combined distributed lag and adaptive expectation models that allows a fair assessment concerning ERPT throughout the time dimension, we reveal evidence that exchange rate changes will be transmitted immediately to increasing domestic prices in the short run. Similarly, increased interest policy, GDP, and trade openness will push consumer prices up in the short term through adaptive expectation mechanisms. However, the pass-through effect tends to decrease in the long run due to a credible ITF implementation. Meanwhile, the pass-through effect concerning trade openness varies across countries in the short run, while openness tends to increase pressures on consumer prices in the long run. This condition allows further investigation to examine the pass-through effect and its transmission to various prices, including prices, imports, export prices, economic structure, and the effect of fear of floating in the ITF.JEL Classification: E31, E52, E58, F31, F41How to Cite:Kurnia, A. S., & Sugiyanto, FX. (2023). Exchange Rate Pass-Through and Economic Openness Under Inflation Targeting Framework in Asian ITF Economies. Etikonomi, 22(2), 357 – 368. https://doi.org/10.15408/etk.v22i2.30967.